PERBANDINGAN SOSIAL DALAM KONSUMSI KONTEN INSTAGRAM DAN TIKTOK: KONSTRUKSI BODY IMAGE DAN KEPERCAYAAN DIRI MAHASISWI BERHIJAB - Robby Rachman Nurdiantara; Sitti Maesurah (AN-NISA, 2026)
The increasing use of Instagram and TikTok has made these platforms an integral part of female students’ daily lives, including in shaping their social comparison experiences. This phenomenon is particularly relevant among hijab-wearing female students who navigate the intersection of Islamic values and digital culture on social media. This study aims to explore social comparison experiences in Instagram and TikTok content consumption and their implications for body image and self-confidence among hijab-wearing female students in Bandung, Indonesia. Employing a qualitative phenomenological approach, the study draws on Festinger’s Social Comparison Theory and the body image framework proposed by Cash and Pruzinsky. Data were collected through in-depth interviews with active Instagram and TikTok users and analyzed using the interactive model of Miles and Huberman. The findings reveal that social media is perceived as a source of information, inspiration, and entertainment, while simultaneously serving as a space for self-comparison. Social comparison extends beyond physical appearance to include academic achievement, career aspirations, and lifestyle. These experiences influence how participants perceive their bodies and develop self-confidence, functioning both as sources of pressure and self-empowerment. Furthermore, the hijab emerges as a site of negotiation between religious values and digital cultural representations, with Islamic values fostering self-acceptance and reflective interpretations of social comparison experiences. The study concludes that social comparison on social media is a dynamic process shaped by the interaction between digital representations, personal experiences, and the religious values held by hijab-wearing female students